Study on Tobacco Control-Related Stakeholders’ Perspective on Tobacco Control Policies and Practice Towards Teenagers and Children Under Sharia Law Setting in Aceh - Hasnur, Hanifah; Septiani, Riza; Arifin, Vera Nazhira; Presilawati, Febyolla; Aletta, Alma; Helfianti, Sutri; Muhammad, Muhammad; Lastri, Surna; Perdana, Luthfi Nanda; Zahara, Meutia; et al. (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
Banda Aceh City Qanun Number 5 of 2016 concerning Smoking Free Areas and MPU Fatwa Number 18 of 2014 concerning Smoking in the Islamic view are two regional policies that have been issued and must be implemented optimally to limit and reduce smoking consumption, especially among adolescents and children in Aceh. This study aims to assess the perspectives of tobacco control-related stakeholders on tobacco control policies and practices in Aceh Province for children and adolescents. This study uses a qualitative study design by conducting Focus Group Discussions with twelve people as representatives of stakeholders related to tobacco control efforts in Aceh. The smoking culture of the Acehnese people which has integrated into their way of life has made teenagers and children vulnerable to exposure to cigarettes. But on the other hand, the Islamic view of smoking is in line with the principles of tobacco control where smoking can harm children and adolescents, so it is strictly prohibited in the Islamic view. Therefore, it is suggested that tobacco control interventions in Aceh for children and adolescents can focus on interventions that use a socio-cultural approach. This can guarantee the success of the tobacco control intervention program carried out in certain areas such as Aceh Province, which still has very clear socio-cultural values. In addition, a shared understanding of the dangers of smoking and making clear the law against smoking will strengthen tobacco control in Aceh, where so far the people have carried out everything based on sharia. Strict sanctions for youth and children who smoke and adequate resources are other keys to the success of the practice and implementation of tobacco control policies in Aceh Province.